2022
DOI: 10.7202/1093886ar
|View full text |Cite
|
Sign up to set email alerts
|

L’expérience des participantes au programme STEP : une intervention prénatale pour les femmes ayant subi de mauvais traitements durant leur enfance

Abstract: L'expérience des participantes au programme STEP : une intervention prénatale pour les femmes ayant subi de mauvais traitements durant leur enfance Résumé Contexte : Le programme STEP est une intervention prénatale de groupe destinée aux femmes enceintes ayant vécu des traumatismes interpersonnels au cours de leur enfance tels que la maltraitance. La présente étude vise à décrire l'expérience des participantes de leur participation au programme. Méthodologie : Des entretiens individuels ont été réalisés auprès… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…Our findings that a brief online intervention could contribute to mitigating psychological distress and post-traumatic symptoms, increasing positive affectivity, enhancing resilience, improving the quality of the relationship with the partner and supporting a more positive view of self in pregnant women during the COVID-19 pandemic has important implications for clinical practice and public health. The results also offer additional support concerning the acceptability of STEP programs 48,49 and the effectiveness of mentalization-based interventions during the prenatal period 22,[50][51][52] .…”
Section: Discussionmentioning
confidence: 68%
“…Our findings that a brief online intervention could contribute to mitigating psychological distress and post-traumatic symptoms, increasing positive affectivity, enhancing resilience, improving the quality of the relationship with the partner and supporting a more positive view of self in pregnant women during the COVID-19 pandemic has important implications for clinical practice and public health. The results also offer additional support concerning the acceptability of STEP programs 48,49 and the effectiveness of mentalization-based interventions during the prenatal period 22,[50][51][52] .…”
Section: Discussionmentioning
confidence: 68%
“…In the current study, 40 participants (95%) received the online version. Previous research showed that women who participated in the program reported high levels of satisfaction across all of the sessions, a significant decrease in psychological distress (Berthelot et al., 2021) and generally considered that the program met their needs, namely owing to the pertinence of the activities, the secure framework and the group format (Berthelot, Goupil, et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Mots-clés : pleine conscience, grossesse, détresse psychologique, compétence maternelle, relation mèreenfant Matériel supplémentaire : https://doi.org/10.1037/cbs0000376.supp L'adaptation à la maternité constitue un défi de taille pour les femmes en contexte de vulnérabilité, condition décrite comme résultant de facteurs physiques, sociaux, économiques ou environnementaux (Berthelot et al, 2016; Institut de la statistique du Québec, 2016) mais également pour celles ne présentant pas de facteurs de risque particuliers (Hamelin-Brabant et al, 2015). En effet, Roch et al (2016) expliquent qu'une clientèle universelle peut voir son équilibre rompu en période périnatale, notamment en raison d'événements imprévus (séparation, perte d'emploi), de la personnalité du parent et de la façon avec laquelle il s'adapte aux changements, du déroulement de la grossesse et de l'état de santé de l'enfant à la naissance.…”
unclassified